Altered Amygdala Development and Fear Processing in Prematurely Born Infants - Cismaru, Anca Liliana; Gui, Laura; Vasung, Lana; Lejeune, Fleur; Barisnikov, Koviljka; Truttmann, Anita; Borradori Tolsa, Cristina; Hüppi, Petra S. (Frontiers in Neuroanatomy, 2016)
Context: Prematurely born children have a high risk of developmental and behavioural disabilities. Cerebral abnormalities at term age have been clearly linked with later behavior alterations, but existing studies did not focus on the amygdala. Moreover, studies of early amygdala development after premature birth in humans are scarce. Objective: To compare amygdala volumes in very preterm infants at term equivalent age (TEA) and term born infants, and to relate premature infants’ amygdala volumes with their performance on the Laboratory Temperament Assessment Battery (Lab-TAB) fear episode at 12 months. Participants: 81 infants born between 2008 and 2014 at the University Hospitals of Geneva and Lausanne, taking part in longitudinal and functional imaging studies, who had undergone a magnetic resonance imaging (MRI) scan at TEA enabling manual amygdala delineation. Outcomes: Amygdala volumes assessed by manual segmentation of MRI scans; volumes of cortical and subcortical gray matter, white matter and cerebrospinal fluid (CSF) automatically segmented in 66 infants; scores for the Lab-TAB fear episode for 42 premature infants at 12 months. Results: Amygdala volumes were smaller in preterm infants at TEA than term infants (mean difference 138.03 mm3, p<0.001), and overall right amygdala volumes were larger than left amygdala volumes (mean difference 36.88 mm3, p<0.001). White matter volumes were significantly smaller (p<0.001) and CSF volumes significantly larger (p<0.001) in preterm than in term born infants, while cortical and subcortical gray matter volumes were not significantly different between groups. Amygdala volumes showed significant correlation with the intensity of the escape response to a fearsome toy (rs=0.38, p=0.013), and were larger in infants showing an escape response compared to the infants showing no escape response (mean difference 120.97 mm3, p=0.005). Amygdala volumes were not significantly correlated with the intensity of facial fear, distress vocalisations, bodily fear and positive motor activity in the fear episode. Conclusion: Our results indicate that premature birth is associated with a reduction in amygdala volumes and white matter volumes at TEA, suggesting that altered amygdala development might be linked to alterations in white matter connectivity reported in premature infants. Moreover, our data suggests that such alterations might affect infants’ fear-processing capabilities.